THE INCREASING OF WOMEN EMPLOYEES PERFORMANCE ON WORK FROM HOME AND WORK LIFE BALANCE IN COVID 19 PANDEMIC ERA - Betty Magdalena; Zuriana Zuriana; Suwandi Suwandi; Ricka Dita Agata (Prosiding International conference on Information Technology and Business (ICITB), 2020)
The purpose of this study was to determine the performance improvement of female employees from the work from home and the work-life balance on the performance of female employees of PT. Perkebunan Nusantara VII. The number of samples was forty-five respondents using associative research methods. It looked for causal effects among the independent variables. They were work from home (X) and the moderating variable, namely the work-life balance (Z) to the dependent variable, namely the performance of female employees (Y). The method of data processing used the SmartPLS Ver.3 method. The result of this study showed that work from home had a significant effect on the performance of female employees of PT. Perkebunan Nusantara VII and the work-life balance moderated the effect of work from home on the performance of female employees and significantly. In other words, the work-life balance had a positive effect on the performance of female employees. Furthermore, the work-life balance factor was needed to encourage the relationship between the two, because the work-life balance in this case actually strengthened the effect of work from home on the performance of female employees of PT. Perkebunan Nusantara VII.Keywords:Work from Home, Work Life Balance, Female Employee Performance, Covid-19